Correction To: Validation of the Short Version (tls-15) of the Triangular Love Scale (tls-45) Across 37 Language - Dinić, Bojana M.; Sorokowski, Piotr; Toplu Demirtaş, Ezgi; Frederick, David A.; Pisanski, Katarzyna; Kowal, Marta; Gjoneska, Biljana; Sternberg, Robert J. (Springer, 2023)
Love is a phenomenon that occurs across the world and affects many aspects of human life, including the choice of, and process of bonding with, a romantic partner. Thus, developing a reliable and valid measure of love experiences is crucial. One of the most popular tools to quantify love is Sternberg’s 45-item Triangular Love Scale (TLS-45), which measures three love components: intimacy, passion, and commitment. However, our literature review reveals that most studies (64%) use a broad variety of shortened versions of the TLS-45. Here, aiming to achieve scientific consensus and improve the reliability, comparability, and generalizability of results across studies, we developed a short version of the scale—the TLS-15—comprised of 15 items with 5-point, rather than 9-point, response scales. In Study 1 (N = 7,332), we re-analyzed secondary data from a large-scale multinational study that validated the original TLS-45 to establish whether the scale could be truncated. In Study 2 (N = 307), we provided evidence for the three-factor structure of the TLS-15 and its reliability. Study 3 (N = 413) confirmed convergent validity and test–retest stability of the TLS-15. Study 4 (N = 60,311) presented a large-scale validation across 37 linguistic versions of the TLS-15 on a cross-cultural sample spanning every continent of the globe. The overall results provide support for the reliability, validity, and cross-cultural invariance of the TLS-15, which can be used as a measure of love components—either separately or jointly as a three-factor measure.
Keywords: Cross-cultural; Triangular theory of love; Triangular love scale